Analysis Of The Effect Of Rainfall On The Corrosion Rate Of Car Frames In 10 Regions In Indonesia That Have High Rainfall Levels - arvian enggal putra; togu juliman manulang; stepeen binsar manurung; willy brodus nimo; Fardin Hasiubuan (METALOGRAM, 2026)
This study aims to understand how much rainfall affects damage (corrosion) to car frames in 10 regions in Indonesia that are often hit by heavy rain. The car's frame is essential for the strength and safety of the vehicle, but it can be severely damaged by corrosion. In Indonesia, which has a tropical climate with high rainfall, rainwater can accelerate corrosion because it acts as a "carrier" of destructive substances from the air. We will collect rainfall data from 10 selected locations and test pieces of steel (similar to car frame materials) in those locations for a minimum of 6 months. After that, we will measure how much the steel has reduced in weight (due to corrosion) and see changes to its surface. We will also analyze rainwater content (such as acidity and salt content) to find out what substances accelerate corrosion. The collected data will be statistically processed to see the relationship between rainfall and corrosion velocity, as well as the role of other environmental factors. It is hoped that the results of this study will provide a clear understanding of how corrosion occurs in the tropics of Indonesia and provide practical advice to protect the car frame, so that the car can be more durable and safe.